Pharmacological Properties, Molecular Mechanisms, and Pharmaceutical Development of Asiatic Acid: A Pentacyclic Triterpenoid of Therapeutic Promise - Nagoor Meeran, Mohamed Fizur; Goyal, Sameer N.; Suchal, Kapil; Sharma, Charu; Patil, Chandragouda R.; Ojha, Shreesh K. (Frontiers in Pharmacology, 2018)
Asiatic acid (AA) is a naturally occurring aglycone of ursane type pentacyclic triterpenoids from a tropical plant, Centella asiatica, reputed in traditional medicine for wound healing, neurodegenerative diseases and cancer. AA possesses numerous pharmacological activities such as antioxidant and anti-inflammatory and regulates apoptosis, which contribute to its therapeutic effects. It also showed antihypertensive, nootropic, antimicrobial and antitumor activities in preclinical studies. AA has been found to affect many enzymes, receptors, growth factors, transcription factors, apoptotic proteins and cell signaling cascades. This review comprehensively represents the available scientific reports on therapeutic potential and the underlying pharmacological and molecular mechanisms of AA. The review also deliberates pharmacokinetics, physicochemical properties, analysis and structural modifications in the pharmaceutical development of AA. The article also discusses the challenges and prospects on the pharmaceutical and clinical development of AA with a pharmacological basis of its use in therapeutics against numerous diseases inducing cardiovascular, neurological, dermatological, rheumatic, gastrointestinal, and metabolic and malignancy. The article also emphases on the pharmacokinetics, physicochemical properties, drug delivery and ways of its pharmaceutical development as an agent or adjuvant along with currently used modern medicines to maximise efficacy and safety. Based on the available literature highlighting the pharmacological properties, therapeutic potential and molecular mechanisms AA appears one of the important pleiotropic multitargeted agent of natural origin for further pharmaceutical development and clinical application.